2020
DOI: 10.1002/aoc.5772
|View full text |Cite
|
Sign up to set email alerts
|

Binuclear titanium complexes coordinated by rigid p‐phenylene linked bis‐β‐carbonylenamine: Synthesis, structure, ethylene polymerization and copolymerization with 1,5‐hexadiene

Abstract: Binuclear complexes for olefin polymerization have attracted great attention due to their unique catalytic properties compared with their mononuclear counterparts. Here a series of p‐phenylene‐bridgedbis‐β‐carbonylenamine ligands and their binuclear Ti complexes Ti2L1–Ti2L3 were prepared and characterized by 1H NMR, 13C NMR, Fourier transform infrared spectroscopy, and elemental analysis. The binuclear complex Ti2L3 bearing an octylthio sidearm was further investigated by single‐crystalX‐ray diffraction, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…During the last three decades, metallocene-catalyzed ethylene/diene copolymerization has emerged as an efficient method towards post-functionalized- [1,2,3,4,5,6] and long-chain branched (LCB) polyethylene (PE) [7,8,9,10,11,12,13,14,15,16,17]. The latter aspect proved particularly interesting, since LCB-PEs most often exhibit significantly better processability than their linear counterparts, albeit retaining the excellent mechanical properties (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…During the last three decades, metallocene-catalyzed ethylene/diene copolymerization has emerged as an efficient method towards post-functionalized- [1,2,3,4,5,6] and long-chain branched (LCB) polyethylene (PE) [7,8,9,10,11,12,13,14,15,16,17]. The latter aspect proved particularly interesting, since LCB-PEs most often exhibit significantly better processability than their linear counterparts, albeit retaining the excellent mechanical properties (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Some recent examples of successful application of binuclear titanium complexes for ethylene (co)polymerization are given in previous studies. [3][4][5][6][7] It was previously shown that binuclear and hexanuclear titanium complexes stabilized by a tetradentate derivative of 2-hydroxymethylphenol showed significantly higher catalytic activity and thermal stability in ethylene polymerization in comparison to mononuclear analogue. [8,9] One of the most important factors in the design of binuclear and polynuclear olefin polymerization precatalysts is the distance between the metal centers.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1,2 ] Some recent examples of successful application of binuclear titanium complexes for ethylene (co)polymerization are given in previous studies. [ 3–7 ]…”
Section: Introductionmentioning
confidence: 99%